2019
DOI: 10.3389/fcimb.2019.00324
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Is a Novel Modulator of Bacterial Membrane Vesicles

Abstract: Membrane vesicles (MVs) released from bacteria participate in cell communication and host-pathogen interactions. Roles for MVs in antibiotic resistance are gaining increased attention and in this study we investigated if known anti-bacterial effects of cannabidiol (CBD), a phytocannabinoid from Cannabis sativa, could be in part attributed to effects on bacterial MV profile and MV release. We found that CBD is a strong inhibitor of MV release from Gram-negative bacteria (E. coli VCS257), while inhibitory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 65 publications
4
70
0
1
Order By: Relevance
“…It is proposed that polymyxins permeabilize the outer membrane of Gram-negative pathogens to enable CBG to act on the inner membrane. Similarly, Kosgodage et al found that CBD can act as a sensitizing agent in combination with various antibiotics [66]. For Gram-negative pathogens, CBD strongly inhibited the release of membrane vesicles, which play a role in inter-bacterial communication and the transfer of cargo molecules.…”
Section: Structure-activity Relationships Of Cannabinoidsmentioning
confidence: 95%
“…It is proposed that polymyxins permeabilize the outer membrane of Gram-negative pathogens to enable CBG to act on the inner membrane. Similarly, Kosgodage et al found that CBD can act as a sensitizing agent in combination with various antibiotics [66]. For Gram-negative pathogens, CBD strongly inhibited the release of membrane vesicles, which play a role in inter-bacterial communication and the transfer of cargo molecules.…”
Section: Structure-activity Relationships Of Cannabinoidsmentioning
confidence: 95%
“…In the protozoa Giardia intestinalis, two distinct EV size populations with different functions in host-pathogen interactions have been described [19]. In bacteria, EV profiles from Gram-negative and Gram-positive bacteria have been described in the size range of 10-600 nm and 60-400 nm and were also shown to change with respect to size profile and EV cargo in response to drug-treatment [18,37]. In camelids EVs are reported in llama (Lama glama) plasma in the 40-400 nm range [10].…”
Section: Introductionmentioning
confidence: 99%
“…In camelids EVs are reported in llama (Lama glama) plasma in the 40-400 nm range [10]. In human cancer studies, cellular EV profiles vary between cancer types and change in response to drug-treatment, both with respect to EV size distribution and cargo [25][26][27]37]. A recent study assessing serum EVs from teleost fish (cod, Gadus morhua L.), reported changes in EV release and cargo (deiminated proteins and microRNAs) related to immunological status and growth in response to change in water temperature during rearing [38].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the commercially available agents for reducing bacterial content of dental plaque, several natural herbal extracts, such as pomegranate, algae, triphala, tulsipatra, neem, aloe vera, and cinnamon, have been reported to be effective against dental plaque bacteria [3][4][5][6][7][8][9]. Similarly, cannabinoids extracted from cannabis has been reported to have potential antimicrobial properties against both gram-positive and gram-negative bacterial species [10][11][12]. However, at least to our knowledge, the efficiency of cannabinoids in inhibiting the growth of dental plaque associated bacteria has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%